Short incubation periods of atypical H-type BSE in cattle with EK211 and KK211 prion protein genotypes after intracranial inoculation - Cassmann, Eric D.; Frese, Alexis J.; Becker, Kelsey A.; Greenlee, Justin J. (Frontiers in Veterinary Science, 2023)
In 2006 a case of atypical H-type BSE (H-BSE) was associated with a germline mutation in the PRNP gene that resulted in a lysine substitution for glutamic acid at codon 211 (E211K). The E211K amino acid substitution in cattle is analogous to E200K in humans that develop genetic Creutzfeldt-Jakob disease (CJD). In the present study, we aimed to determine the effect of the EK211 prion protein genotype on the incubation time in cattle inoculated with the agent of H-BSE, characterize the molecular profile of H-BSE in KK211 and EK211 genotype cattle, and assess the influence of serial passage on BSE strain. Eight cattle, representing three PRNP genotype groups (EE211, EK211, and KK211), were intracranially inoculated with the agent of H-BSE originating from a case from a cow with an EE211 prion protein genotype or a cow with an E211K amino acid substitution. All cattle developed clinical disease, post-mortem samples were collected, and prion disease was confirmed with enzyme immunoassay, anti-PrP Sc immunohistochemistry, and western blot. Western blot molecular analysis was distinct in a steer with KK211 H-BSE compared to EK211 and EE211 cattle. Incubation periods were significantly shorter in cattle with EK211 and KK211 genotypes compared to EE211. The inoculum type did not significantly influence the incubation period of cattle. This study demonstrates a shorter incubation period of H-BSE in cattle with the K211 genotype in both the homozygous and heterozygous state.